2021
DOI: 10.1097/brs.0000000000004305
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors on Initial in-brace Correction in Idiopathic Scoliosis

Abstract: While surgery for ASD is beneficial and results in functional improvement, in over 20% of older adults outcomes from surgery are less desirable. 80% of patients agreed that having surgery was the right decision for them, 77% would make the same choice in future, and 21% regretted their choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
1
7
3
Order By: Relevance
“…Although low evidence was found in the association of BMI and in-brace correction in a previous review study [20], this present study found a significant negative correlation between in-brace correction and BMI. Similarly, a study by Goodbody et al [14] concluded that overweight AIS patients had lower results in immediate brace correction as compared to the normal-weight group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although low evidence was found in the association of BMI and in-brace correction in a previous review study [20], this present study found a significant negative correlation between in-brace correction and BMI. Similarly, a study by Goodbody et al [14] concluded that overweight AIS patients had lower results in immediate brace correction as compared to the normal-weight group.…”
Section: Discussioncontrasting
confidence: 99%
“…A study by Lang et al found that in-brace correction was associated with initial Cobb angle, sagittal and coronal balance, and LPR [19]. In the current literature study, strong evidence was found between flexibility and in-brace correction and moderate evidence for curve pattern influencing in-brace correction [20].…”
Section: Discussionsupporting
confidence: 48%
“…Wong et al showed that in-brace correction offers relevant information about structural trunk plasticity [ 11 ]. Thus, a greater curve flexibility can lead to a better brace correction [ 12 ]. However, other spinal and pelvic variables beyond flexibility seem to influence the rate of in-brace correction [ 12 , 13 ], but their predictive role is not well-established.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a greater curve flexibility can lead to a better brace correction [ 12 ]. However, other spinal and pelvic variables beyond flexibility seem to influence the rate of in-brace correction [ 12 , 13 ], but their predictive role is not well-established. A recent systematic review clarified the predictive value of various radiographical variables on brace outcome in AIS subjects, where reduced in-brace correction and <28% supine flexibility were confirmed to be predictors of progression with high and moderate evidence, respectively [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curve type and curve flexibility are the best proven factors influencing this initial in-brace correction, but these patient factors cannot be influenced by the orthotist [ 5 ]. Translations generated by the brace on the thorax generally are statistically and linearly related to corresponding corrections of the spine, and a positive correlation has been reported between the correction of the lumbar scoliosis and correction of the lumbar lordosis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%